Ultra-Sensitive MTB/RIF: Is Trace Detected Diagnostically Helpful, or a Mere False Positive? A 3-year Clinical Audit - Nurnabilah, Zainuddin; Nur Zulieffa, Zakaria; Nor Hafizah, Jentera@Yahya; Abigail Terah, Iben; Alisa Hanum, Arba’eni @ Arbaen; Norashikin, Samsudin (2025)
As a molecular WHOrecommended rapid diagnostic test (mWRD) for tuberculosis (TB), GeneXpert MTB/RIF has been a major gamechanger in the fight against the global pandemic since its introduction in 2010.